Organic Conductors - Naito, Toshio (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This collection of articles focuses on different aspects of the study of organic conductors. Recent progress in both theoretical and experimental studies is covered in this Special Issue. Papers on a wide variety of studies are categorized into representative topics of chemistry and physics. Besides classical studies on the crystalline organic conductors, applied studies on semiconducting thin films and a number of new topics shared with inorganic materials are also discussed.